What’s new in insomnia? Diagnosis and treatment - Pentagna, Álvaro; Castro, Luiz Henrique Martins; Conway, Bárbara Araújo (Arquivos de Neuro-Psiquiatria, 2022)
Although, insomnia is one of the most common diseases that health professionals face in their practice, it receives little attention in medical training. Diagnosis is based on a careful history taking, and physicians must be aware of the diagnostic criteria. Insomnia should not be considered a symptom, but a comorbid condition. Although cognitive behavioral therapy (CBT) has been the mainstay treatment for insomnia for many years, it is usually regarded as a novel therapeutic strategy, both because of scarcity of qualified psychologists and of limited knowledge about insomnia among physicians. GABA receptor acting drugs are being abandoned in the treatment of insomnia because of abuse and dependence potential and accident risk. Two main current therapeutic options with the best scientific evidence are the tricyclic antidepressant, doxepin, and a new melatoninergic receptor agonist, ramelteon. Newer drugs to treat insomnia are in the pipeline. Hypocretine blocking agents will be marketed in the near future.
Keywords: Sleep Initiation and Maintenance Disorders; Cognitive Behavioral Therapy; Hypnotics and Sedatives